2017
DOI: 10.1007/s10068-017-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of peony seed oil on aging mice

Abstract: d-galactose was injected into mice of ages 4-5 months, and peony seed oil was administered using an oral gavage to assess its possible anti-aging functions. The content of malondialdehyde (MDA) and the activities of monoamine oxidase (MAO), glutathione peroxidase (GSH-Px), and superoxide dismutase (SOD) in the brain and liver of these mice were determined using biochemical kits. The significance of the differences in the content of the components associated with aging and anti-aging among each group was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Moreover, DHA‐enriched phosphatidylcholine (DHA‐PC) and EPA‐enriched phosphatidylcholine (EPA‐PC) could moderate cognitive deficits in high‐fat diet‐fed senescence‐accelerated mouse prone 8 mice by restraining Aβ generation, inhibiting oxidative stress and apoptosis, down‐regulating inflammatory response, and enhancing neurotrophic activity 26 . Researches have reported that PSO shows therapeutic effects on anti‐oxidant, 27 hypoglycemic, 23 hypolipidemic, 28 and anti‐aging functions 27 . However, whether PSO can improve the cognitive deficits associated with AD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DHA‐enriched phosphatidylcholine (DHA‐PC) and EPA‐enriched phosphatidylcholine (EPA‐PC) could moderate cognitive deficits in high‐fat diet‐fed senescence‐accelerated mouse prone 8 mice by restraining Aβ generation, inhibiting oxidative stress and apoptosis, down‐regulating inflammatory response, and enhancing neurotrophic activity 26 . Researches have reported that PSO shows therapeutic effects on anti‐oxidant, 27 hypoglycemic, 23 hypolipidemic, 28 and anti‐aging functions 27 . However, whether PSO can improve the cognitive deficits associated with AD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of essential amino acid content in rice, especially lysine content, can significantly improve the nutritional value of rice. Studies have shown that the increase of important nutrients in food can significantly promote the health of the body (Shen & Wu, 2017;Han et al, 2017;Wu et al, 2017). It can be seen that spraying a suitable concentration of the compound nutrient solution during a suitable growth period of rice is a good way to increase the essential amino acid content of rice and improve its nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…Several antioxidants have been reported to be associated with inhibition of cellular senescence [29,30,31]. To examine whether histochrome affects cellular senescence, we investigated the long-term effect of histochrome treatment on an in vitro culture of hCPCs.…”
Section: Resultsmentioning
confidence: 99%